Evaluation of Slagging and Fouling Indices in Boilers, for Steam Power Plant - Prima Aryandi; Jusfarida Jusfarida; Hendra Bahar; Avelyn Shintya Sari; Fairus Atika Redianto Putri; Korchnoi Pasaribu (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2026)
Coal acts as the primary fuel for the boiler at PLTU to support the combustion process. The boiler serves as the main steam generator in this coal-fired power plant. During combustion, coal produces ash that deposits and leads to slagging and fouling, two conditions that reduce boiler efficiency and performance. This study analyses how slagging and fouling affect the performance of Boiler at PLTU. Using a quantitative approach, the research evaluates coal quality data (proximate and ultimate analyses), ash compound content, sulphur levels, and calculates slagging and fouling indices in relation to boiler performance. The results show that the slagging index ranges from 0.15 to 0.77 and the fouling index from 0.19 to 0.48, indicating a low to moderate tendency. When these indices are at their lowest, boiler efficiency reaches 88.05% (direct method) and 86.09% (indirect method). At their highest, efficiency drops to 78.25% and 78.65%, respectively. This decline increases coal consumption for electricity generation. These findings highlight the need for regular inspection of ash content and coal quality to reduce the negative effects of slagging and fouling on overall boiler performance.